Transitioning From a Daily to a Block Didactic Format in a Pediatric Residency Program - Walter Dehority; Amy Staples; Emily Macdonald; Jennifer Maito; Rebecca Rotello; Benjamin Hoffman (MedEdPORTAL, 2012)
Abstract Introduction Prior to 2009, both faculty and housestaff at the University of New Mexico were dissatisfied with the structure of didactic instruction. Housestaff frequently missed daily noon-hour didactic sessions secondary to ongoing clinical duties. If residents were able to attend, both they and faculty presenters were frequently distracted by frequent pages. In response to this global dissatisfaction from housestaff and faculty about these daily noon didactic sessions, we sought to implement an alternative that would allow for truly protected resident time, regular attendance, and improved resident and faculty satisfaction. As a result, didactic instruction was transitioned to a block or “resident school” format, consisting of 4 hours of teaching held 1 day a week. A weekly block didactic format for residents has been utilized by some residency programs to combat many of the challenges that conspire to decrease the efficacy of didactic sessions. Methods This resource describes the rationale and conceptual background for the transition into a block format, and provides instruction and guidance for programs interested in such a change. Example yearly and monthly templates, with the latter grouped by topic, are provided. A detailed discussion of the problems and limitations of the block format are also provided with potential solutions to common problems. Results The introduction of a block didactic format in our Pediatric residency program was associated with significantly increased overall satisfaction when compared with a traditional daily didactic format by both housestaff and faculty. In addition, we witnessed a significant improvement in passage rates for the American Board of Pediatrics Certification examination among our graduates following implementation of the block didactic format, as well as improvements in in-training examination scores. We also demonstrated a 67% improvement in resident attendance with the transition to a block format by insuring that every resident who was eligible to attend did so each week. We demonstrated a significant improvement in resident satisfaction with the quality of faculty presentations after the format change, as well as a significant preference for the block format overall amongst both housestaff and faculty. Discussion We believe our project is the first to assess the impact on faculty and housestaff of a transition from daily didactic sessions to a block didactic format, and the first to describe the implementation of a block didactic format in a program with intensive inpatient and outpatient service obligations. Such a format helps address several barriers to housestaff didactic education such as ongoing patient care and pager call, tasks identified in the literature to be the most likely to interfere with educational activities. This format also helps improve reported compliance with duty hour requirements, presumably because residents are able to focus on efficient clinical care without having to interrupt their workday to attend didactic sessions for all but one day of the week. Further, block didactics increased the punctuality of residents engaged in off-site clinical activities requiring extended travel time.